Museums, the Exhibitionary Complex and State Stability in the Victorian Era - Cécile Doustaly (Angles)
This paper focuses on the different agents, whether public, private or voluntary, who in the Victorian Age campaigned in favour of the opening of public museums, whether national, local or municipal, and who invoked an intrication of cultural, political, social and economic rationales to muster support. In particular, these agents foregrounded the supposed capacity of museums to educate, pacify and control sections of the population considered as a threat to state stability. How were these objects of concern, i.e. the working classes, presented in the different discourses and actions relating to museums, before and after their opening? The Victorian period was one of unstable, shifting social conditions in urban areas, characterised by an increased dynamic of urbanisation, coupled with neighbourhood segregation and related problems (criminality, betting, alcohol).These changes spurred the development of the rational recreation movement, whose support for the creation of public cultural institutions is examined here. The 1851 Exhibition is focused on, insofar as it provided a quite different exhibitionary complex and context, compared to that of museums. 1851 is identified as a turning point of the Victorian Era, involving as it did a shift away from the pacifying function, until then associated with museums. In conclusion, the article examines the factors which enabled these Victorian public museums to attract large number of visits from the working classes, in a context of enduring class distinction. The article draws on primary sources and also on established theories of social control, from that of Bailey (a leisure historian) and Bennett (who drew on Foucault’s approach to apprehend the function of museums), but also on Parrat, Taylor, Kriegel, and, more recently, Jennings, Quinn, Purbrick and Woodson Boulton. The periodization, categorisation of actors, and the typology of museums proposed in this paper allows us to highlight the specific relevance of the conflicting theories regarding the role of museums.